ANALISIS PENGARUH INFLASI, KURS, BI RATE DAN PDB TERHADAP PENERIMAAN JUMLAH MAHASISWA BARU DI KAMPUS STMIK ATMA LUHUR PANGKALPINANG - seno hadi saputro (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
This research is perform to evaluate the influence of inflation, exchange rate, BI Rate and GDP toward the number of new admissions. Microeconomics variable. Methodology research as the sample used purposive sampling and this research in STMIK Atma Luhur Pangkalpinang. Data analysis with multiplier regression of common effect datapanel method in level 3 Diploma and fixed effect datapanel method in bachelor degree. The results obtained are the empirical evidence of analysis show as inflation, exchange rate and BI Rate have a negative influence toward the number of new admissions of level 3 diploma in STMIK Atma Luhur Pangkalpinang and GDP not influence toward the number of new admissions of level 3 diploma in STMIK Atma Luhur Pangkalpinang. While in bachelor degree, inflation, exchange rate, BI rate and GDP not influence toward the number of admissions in STMIK Atma Luhur Pangkalpinang